PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECK TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPS SMAN 1 BAYANG UTARA TAHUN PELAJARAN 2013/2014 - Yuliasari, Nelvi; Husna, Husna; Aima, Zulfitri (STKIP PGRI Sumbar, 2013)
This research was stimulated by the background of lower comprehension of studentâs to mathematic subject that can be seen in semester II at the class X SMAN 1 Bayang Utara. This research aim to know whatever the mathematic concept of studentsâ comprehension through the implementation of cooperative teaching model of Pair Check was better than conventional teaching model. The type of this research was experimental research. Population of this research was the student at the class XI IPS SMAN 1 Bayang Utara period 2013/2014 consisted two classes. Technique of taking sample was done randomly by selecting the classes was XI IPS.1 as experimental class and class was XI IPS.2 as control class. This research used instrument of final test about the studentâs understanding of mathematic concept. The form of test used essay by reliability test score Â = 0,90. Technique of data analysis used t-test. Based on the data analysis showed that both class samples have homogeny and normal distribution. The result of hypothesis P-value = 0,033 < Â = 0,05. Thus the hypothesis in this research was accepted. Therefore can be concluded that the studentsâ comprehention about mathematic concept by using cooperative teaching model type of Pair Check was better than studentsâ comprehention of math concept by using conventional teaching model toward student at the class XI IPS SMAN 1 Bayang Utara period 2013/2014 with the confidence level 95%.